Harga Diri pada Remaja Menengah Putri di SMA Negri 15 Kota Semarang - Lukman Yusuf; Chandra Bagus Ropyanto (Jurnal Keperawatan Diponegoro, 2012)
Self-esteem is a individual appraisal, feeling, view to her self or something related to her self that is expressed to the dimension Significance, Power, Competence,Virtue. This studywas aimedtoidentifythe relationshipbetween Self-Esteem anddietary behaviorin femaleadolescent (age 15-17 years) inSMAN 15 Semarang.Design used in this study are correlational descriptive with cross sectional design. Sampling was stratified random sampling method of 170 respondents and using chi-square analysis. The results of the study note that as many as 113 respondents (66.9%) had high self esteem and 57 respondents (33.1) has a low self esteem.Foryoung womenwhowant togo on a dietshould pay attention tonutrition, health andnurses canplay a roleasan educator andcounselor